Effect of chemical treatment on the structural, thermal, and mechanical properties of sugarcane bagasse as filler for starch‐based bioplastic. Issue 3 (8th September 2022) - Hamin, Siti Hajar; Sayid Abdullah, Sharifah Hanis Yasmin; Lananan, Fathurrahman; Abdul Hamid, Siti Hajar; Kasan, Nor Azman; Mohamed, Nurul Najidah; Endut, Azizah
Abstract: BACKGROUND: The demand for green products is pushing industries to search for more eco‐friendly materials, especially for food packaging applications. Starch biopolymer has been recognized as biodegradable material that can be produced from various plants. However, the strength of starch‐based bioplastic retards their widespread application. Simultaneously, the high amount of agricultural waste produced by the food industry has been a growing environmental issue. Incorporating agro‐waste fibers as a biofiller in starch‐based bioplastic can improve the properties of the bioplastic, allowing its use in various applications. Thus, this study aims to evaluate the effect of chemical treatment on the structural, thermal, and mechanical properties of sugarcane bagasse as filler for starch‐based bioplastic. RESULTS: Results showed that alkaline treatment improved surface roughness and freed it of surface impurities. Results revealed that the thermal stability and mechanical properties improved significantly with the incorporation of sugarcane bagasse (SB) loading into potato starch (PS). The highest tensile strength (5.30 MPa) and Young's modulus (28.72 MPa) were exhibited by the sample with 6% SB loading and further increments of SB led to a decrease in the strength of the biopolymer. CONCLUSION: The incorporation of alkali‐treated SB could increase and enhance the tensile strength and thermal stability of the bioplastic. This would contribute to reinforced materials that will allow for the application of PS as a new potential biodegradable material. Thus, it reduces the disposal period process and has great potential as an environmentally friendly, biodegradable, and renewable material. © 2022 Society of Chemical Industry (SCI).